Phenols, Volatiles and Sensory Properties of Primitivo Wines from the “Gioia Del Colle” PDO Area - Trani, A.; Verrastro, V.; Punzi, R.; Faccia, M.; Gambacorta, G. (South African Journal of Enology and Viticulture, 2016)
The aim of this study was to characterise the phenol, anthocyanin, volatile and sensory profiles of Primitivo wines. The wines were produced in three wineries located in the Gioia del Colle PDO (Protected Designation of Origin) area (Southern Italy – Apulia Region). The grapes came from three vineyards of different ages and were grown according to different training systems. The winemaking techniques applied also differed in some technological variables. The results obtained showed that all wines had a high alcohol content (15 to 16% v/v) and were rich in total phenols and proanthocyanidins. The anthocyanin profile was characterised by the prevalence of non-acylated forms, of which malvidin-3-O-monoglucoside accounted for 62 to 67% of the total anthocyanin, followed by the coumarate, acetate and caffeate forms. The volatile fraction was constituted mainly alcohols and esters, the latter having concentrations above the odour threshold. From a sensory point of view, all wines were judged positively, and presented high olfactory and gustatory persistence. The main odour attributes found were soft fruits, cherry and cloves.